Praktik Jual Beli Ijazah dalam Perspektif Hukum Islam: The Practice of Selling and Purchasing Degrees in The Perspective of Islamic Law - Ahmad Syaripudin; Sulkifli Herman; Irfansyah, Irfansyah (TIJARAH: Jurnal Ekonomi, Manajemen, dan Bisnis Syariah, 2024)
The research in this thesis aims to know and understand the Practice of Selling and Buying Diplomas in the Perspective of Islamic Law. The problems to be examined are how Islamic law views the practice of buying and selling diplomas, analysis of buying and selling diplomas according to Islamic business, analysis of the consequences of buying and selling diplomas. In this research, library research is library research which aims to determine the legal status of the practice of buying and selling diplomas, and then analyzing the practice of buying and selling diplomas through a normative approach and elaborated with buying and selling theory, Islamic business ethics and the rules of the Koran, hadith, or the opinion of scholars. . From the overall discussion of research results in accordance with the formulation of the problem and objectives in this study, it shows that the practice of buying and selling diplomas is a crime and a criminal act as a crime of forgery of letters. A diploma is equated with a letter (geschrift) because a diploma creates recognition or rights to an academic degree, or is an acknowledgment of one's achievements listed on the diploma sheet. And it can be concluded that the practice of buying and selling diplomas is an illegal buying and selling practice because the pillars and buying and selling are not fully fulfilled and are buying and selling that are prohibited by Islamic law and not in accordance with Islamic business ethics. In addition, the practice of buying and selling diplomas is also an act that violates the law, namely Article 263 of the Criminal Code and Law no. 20 of 2003 concerning the National Education System.